First snake record from the Sarmiento Formation at La Gran Hondonada (Chubut Province, Argentina) (Ameghiniana, 2012)
The described indeterminate boid snake was collected in rocks belonging to the Sarmiento Formation and exposed at La Gran Hondonada (Chubut Province, Argentina). This is the first snake record for the mid–late Eocene Mustersan South American land-mammal age. The specimen proves that medium- to large-sized boids inhabited the Patagonian region during most of the Palaeogene, suggesting climatic conditions warmer than those established at the beginning of the Neogene.Resumen. PRIMER REGISTRO DE SERPIENTES EN LA FORMACION SARMIENTO, GRAN HONDONADA (PROVINCIA DE CHUBUT, ARGENTINA). El boideo indeterminado descripto en este trabajo fue hallado en sedimentitas de la Formación Sarmiento aflorantes en la localidad La Gran Hondonada (Provincia del Chubut, Argentina). Éste es el primer registro de serpientes para la Edad mamífero Mustersense (Eoceno medio–tardío). El espécimen evidencia que boideos de mediano a gran tamaño habitaron en la región patagónica durante la mayor parte del Paleógeno, sugiriendo condiciones climáticas más cálidas que aquellas desarrolladas a partir del Neógeno.